PENGARUH BUDAYA ORGANISASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA GURU DIMODERASI IKLIM ORGANISASI (Studi Pada Guru SMP Di Kecamatan Ulujami Kabupaten Pemalang) - Samsudin, 1352020037; Liana, Lie (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study was to investigate the influence of organizational culture and work motivation on the performance of teachers with organizational climate is moderated. Population and sample are SMP teacher who has been a civil servant in the District Pemalang Ulujami consisting of five (5) school of 128 teachers. From a population of 128 teachers, all members of the population used as a sample with saturated sampling technique. The research data is primary data obtained directly from the respondents to the questionnaire. The research method uses computer software approach using SPSS for Windows version 21. The method of data analysis using Moderation Regression Analysis (MRA) type quasi moderator. From the test data and analysis conducted this study provide empirical evidence as follows: (1) Cultural Organization positive effect on teacher performance; (2) Work Motivation positive effect on teacher performance; (3) Climate organization significant positive effect on the performance of teachers; (4) Organizational Climate does not moderate the influence of organizational culture on teacher performance and (5) Organizational Climate moderating influence on the performance of teachers work motivation. Theoretical implications, and recommendations for future research are also discussed in the final part in this study.Keywords: Organizational Culture, Work Motivation, Organizational Climate and Teachers Performance